Engaging Patients in Decision-Making and Behavior Change to Promote Prevention - Krist, Alex H; Tong, Sebastian T; Aycock, Rebecca A; Longo, Daniel R (Studies in health technology and informatics, 2017)
Effectively engaging patients in their care is essential to improve health outcomes, improve satisfaction with the care experience, reduce costs, and even benefit the clinician experience. This chapter will address the topic of patient engagement directly and review the relationships between health literacy and patient engagement. While there are many ways to define patient and family engagement, this chapter will consider engagement as "patients, families, their representatives, and health professionals working in active partnership at various levels across the health care system - direct care, organizational design and governance, and policy making - to improve health and health care [1]." We will specifically focus on the patient engagement and health literacy needs for three scenarios (1) decision-making, (2) health behavior change, and (3) chronic disease management; we will include the theoretical underpinnings of engagement, the systems required to better support patient engagement, how social determinants of health influence patient engagement, and practical examples to demonstrate approaches to better engage patients in their health and wellbeing. We will close by describing the future of patient engagement, which extends beyond the traditional domains of decision-making and self-care to describe how patient engagement can influence the design of the healthcare delivery system; local, state, and national health policies; and future research relevant to the needs and experiences of patients.